MENCIPTAKAN GREEN BRAND PERSONALITY BAGI MEREK RAMAH LINGKUNGAN - Suparna, Gede; Ekawati, Ni Wayan; Suasana, I Gusti Agung Ketut Gede; Sriathi, Anak Agung Ayu (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 12 Nomor 2 Tahun 2018DO - 10.24843/MATRIK:JMBK.2018.v12.i02.p07, 2018)
The purpose of this research is to explain the influence of green brand to green brand personality, the influence of green brand toward green brand image, the influence of green brand image on green brand personality, the role of green brand image as mediating the influence of green brand on green brand personality. The study was conducted on the community in Bali, using individual samples as an analysis unit of 110 respondents. The analysis technique used is quantitative analysis based on multivariate analysis using structural equation modeling model based on AMOS 7.0. The results of the analysis found that there is influence of green brand on green brand personality and green brand image, there is influence of green brand image to green brand personality, and green brand image does not act as mediation variable.